Symplocos zizyphoides - Tsen, S.; Matusin, D.; Damit, A.; Khoo, E.; Maryani, A.; Colin Ruzelion Maycock; Nilus, R.; Sugau, J.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2021)
Symplocos zizyphoides is a treelet, endemic to Sabah. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are both 32 km2. There is no major threat as the species is recorded abundantly in Mount Kinabalu. It is assessed as Least Concern. Symplocos zizyphoides is endemic to Sabah, Malaysia. It is known from Mount Kinabalu, Ranau.